Rancang Bangun Aplikasi Audit Internal Fakultas (Studi Kasus: FMIPA Universitas Lampung) - Desrizal Dwi Ayu; Tristiyanto; Aristoteles (Jurnal Pepadun, 2023)
Evaluation of faculty performance is an assessment of the quality of a faculty at the University. This Accreditation Assessment is carried out internally as well as externally by the National Accreditation Board for Higher Education (BAN PT). The Faculty of Mathematics and Natural Sciences is one of the faculties at the University of Lampung, where faculty accreditation is the most important educational support used as an assessment criterion, namely vision, mission, objectives, student archives, and others. The amount of data is one of the problems faced by faculties in storing accreditation data. Referring to the above problems, it is appropriate to develop an "Faculty Performance Evaluation Information System and the University of Lampung Study Program Implementation Unit using the Laravel Framework" which can facilitate the process of searching for the archives and data needed. This information system was built using the prototype method with three stages, namely Listen To Customer (at this stage the system requirements analysis process is carried out based on customer requirements), Build/Revise Mock Up (at this stage the design and coding process is carried out according to customer requests), and Test Drives Mock Up (at this stage testing the system that has been made to the user is carried out). The coding for the development of this system uses the PHP programming language and to simplify the coding process for the Laravel framework design. The testing method used on this system uses the Black Box Testing method with the Equivalence Partitioning type. The result of this study is a Web-Based Faculty Performance Evaluation Information System that can facilitate staff in inputting the required data.